The Effectiveness of Teaching Speaking by Using Drilling Method through YouTube - Herdianti Rochmana Putri (Universitas Muhammadiyah Gresik, 2022)
The purpose of this study is to improve students’ speaking skills by using the drilling method through YouTube. The problem of this study is Does the use of the drilling method on YouTube enhance students'' speaking skills. In this study, the researcher will try to analyze students'' speaking skills. Based on the independent sample t-test and paired sample t-test, it is found out that there is a significant difference between the experimental group using YouTube in the drilling learning method and the control group using conventional media in the drilling learning method. The researcher utilizes Quasi-experimental as a method in this study. The result of paired sample t-test shows the positive correlation between the results in the experimental group. Based on the results of the research described it can be concluded that there is a significant positive influence in the use of YouTube on learning speaking using the drilling method for class XI students of SMA YPI Darussalam. Students will have pretest and posttest to check their skill. Especially in their fluency, vocabulary, grammar, and pronunciation